Clinical Outcome of Eosinophilia in Patients with COVID-19: A Controlled Study : Eosinophilia and COVID -19 - Nair, Arun Prabhakaran; Soliman, Ashraf; Al Masalamani, Muna A.; De Sanctis, Vincenzo; Nashwan, Abdulqadir J.; Sasi, Sreethish; Ali, Elrazi A.; Hassan, Ola A.; Iqbal, Fatima M.; Yassin, Mohamed A. (Acta Biomedica Atenei Parmensis, 2020)
Background: Eosinophils can be considered as multifunctional leukocytes that contribute to various physiological and pathological processes depending on their location and activation status. There are emerging eosinophil-related considerations concerning COVID-19. Variable eosinophil counts have been reported during COVID-19. Whether these changes are related to the primary disease process or due to immunomodulation induced by the treatment has not yet been elucidated. Aim of the study: To describe changes in the differential leukocyte counts including eosinophils, in a cohort of symptomatic patients with confirmed COVID-19 and to correlate these changes, if any, with the severity of the disease. Patients and methods: We recorded the clinical data, lab findings, including inflammatory markers and leukocyte and differential count, course of the disease and severity score in 314 confirmed symptomatic cases of COVID-19. Results: Laboratory tests revealed that 28.7 % (n =86) had mild eosinophilia (eosinophil count > 500 8,000/µL), and 7 (2.3%) had decreased ANC (< 1,500/µl). Seven patients (2.3%) had lymphopenia ( 4,000/µL). C-reactive protein (CRP) was elevated in 83 patients (27.6%). Chest X-Ray changes included: increased broncho vascular markings (38%), ground-glass opacity (GGO) pneumonitis (19.3%), lobar consolidation (5%), bronchopneumonia (8.3%), nodular opacity (1%), acute respiratory distress syndrome (ARDS) (2.3%), pleural effusion (1.0%) and other atypical findings (6.6%). Patients with eosinophilia had significantly lower CRP, and lower % of GGO, lobar and bronchopneumonia and ARDS in their chest images compared to patients without eosinophilia (p: